FROM THE HISTORY OF ORIGIN OF ENGLISH AND UZBEK FEMALE NAMES (Scientific journal of the Fergana State University, 2023)
This article studies the historical path of development of women's personal names and surnames - anthroponyms in English and Uzbek. Particular attention is paid to the origin of anthroponyms, the peculiarities of their formation, various historical processes that had a direct impact on their formation at important stages of history. The article presents the most common personal names in different historical periods. The relevance of the article is determined by the fact that the anthroponyms reflect the morphological and semantic tendencies acting in the language, which makes it possible to trace the linguistic facts in their direct functioning.